Electricity Management in Maharashtra : An Introductory Exposition - Ghorude, K. N. (Prabandhan: Indian Journal of Management, 2011)
Maharashtra is one of the most industrialized states in India. In Maharashtra, since 2005, The Maharashtra State Electricity Distribution Company Limited (MSEDCL) has been unable to supply electricity as per the demand. The state utility has been resorting to load shedding to bridge the gap between supply and demand. Several parts of the state have ten to twelve hours of load shedding. In Maharashtra, load shedding has persisted for the last four-five years and it is expected to continue for a few more years. The Maharashtra State Electricity Distribution Company Limited estimates that the shortages will be continuing till 2011-12.This Paper attempts to highlight some of the major concerns and issues of the prevailing Maharashtra's electricity load shedding. Besides, it examines the trends of government expenditure on energy generation projects, sources of energy generation and consumption pattern, Peak demand, Transmission and losses. It also covers the significance of rural electrification, energy conservation programme and finally suggested Measures / Strategies to overtake the prevailing crisis. Energy is one of the essential infrastructures in the process of economic and social development. India ranks the world's sixth largest energy consumer accounting for about 3.5% of the world's total annual energy consumption, but, per capita consumption of energy is very low at 631 kwh as compared to world consumption of 2873 kwh which needs to be increased to meet the goals of economic and social development. Load shedding results in disruption of lifestyle, huge loss of production in Industrial, Agricultural, services sectors and causes inconvenience to consumers. Besides, it creates Social Problems, law and order Issues and adversely affects different segments of the economy. Naturally, load shedding is one of the major contentious and controversial issues.